1979
DOI: 10.1051/apido:19790305
|View full text |Cite
|
Sign up to set email alerts
|

The Pollen Spectrum of the Honey of Tetragonisca Angustula Angustula Latreille (Apidae, Meliponinae)

Abstract: SUMMARYThose honeys which were microscopically analysed presented a reasonably large number of pollen forms — a total of 55 in 23 samples. The pollen spectrum analysis of two colonies observed indicated that the bees from these colonies were attracted by the same floral supplies, though in different places, at a distance of around 140 meters from one another. The majority of the pollen grains were classified as isolated pollen. In the dominant pollen class were included : Alchornia triplinervia, Eucalypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
10

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 3 publications
1
34
0
10
Order By: Relevance
“…), Passifl ora jilekii Wawra (Passifl oraceae), Piper mollicomum Kunth (Piperaceae), Schizolobium_parahyba Vell (Caesalpiniaceae), Tibouchina granulosa Cogn. (Melastomataceae) e Trema micrantha Blume (Ulmaceae), também foram citados por autores como fontes de pólen para essa abelha (Iwama & Melhem 1979, Lorenzon et al 2006.…”
Section: Nota Científi Ca / Scientifi C Noteunclassified
“…), Passifl ora jilekii Wawra (Passifl oraceae), Piper mollicomum Kunth (Piperaceae), Schizolobium_parahyba Vell (Caesalpiniaceae), Tibouchina granulosa Cogn. (Melastomataceae) e Trema micrantha Blume (Ulmaceae), também foram citados por autores como fontes de pólen para essa abelha (Iwama & Melhem 1979, Lorenzon et al 2006.…”
Section: Nota Científi Ca / Scientifi C Noteunclassified
“…Ramalho et al (1991) mentioned as the most important pollen types of honeys in the state of São Paulo the taxa Cecropia, Citrus, Eucalyptus, Paspalum and Syagrus. The pollen in honeys of Meliponinae presented a very rich and heterogeneous spectrum of plant taxa, in special Alchornea, Eucalyptus, Petroselinum and Schinus (Iwama & Melhem, 1979;Ramalho, 1990).…”
Section: Southeast Regionmentioning
confidence: 99%
“…In a honey sample of the "uruçu" Meliponidae from Bahia , dominant pollen grains came from Eucalyptus and Psidium, together with Bauhinia, Caesalpiniaceae and the Mimosa verrucosa type. Several studies of honey samples of Meliponinae in the state of São Paulo (Guibu et al, 1988;Iwama & Melhem, 1979;Ramalho, 1990;Ramalho et al, 1985) reported great number of flowering species visited by the bees, but selectively, Alchornea, Arecaceae, Eucalyptus, Moraceae, Myrtaceae, Petroselinum and Schinus.…”
Section: Honey and Pollen Of Meliponinaementioning
confidence: 99%
“…Assim, a análise polínica do mel é um importante instrumento para o reconhecimento das plantas apícolas utilizadas pelas abelhas, como suprimento de néctar e pólen [7,34,37].…”
Section: -Introduçãounclassified